Time in Service of Orientalism: The Case of Polish Japanomania at the Turn of the Twentieth Century - Łuksza, Agata (1983– ) (Instytut Historii im. Tadeusza Manteuffla Polskiej Akademii Nauk, 2024)
In this article, I investigate Japanomania – the European and American fascination with Japan from the 1860s to the 1910s – focusing on how Western conceptions of time determined perceptions of Japanese culture. Drawing on Edward Said’s Orientalism and Stuart Hall’s conception of ‘the West’ as a historical construct, I claim that Western understandings of time were instrumental in disseminating Orientalism, framing the East as exotic, static, and timeless. The study centres on Japanomania in turn-of-the-century Warsaw, including the reception of Japanese exhibitions and theatre performances, showing that the modern concept of time was a crucial tool of Orientalism. Specifically, the idea of ‘universal’ time allowed for comparisons between cultures, positioning non-Western societies as inferior and preserving Western hierarchies and narratives. The article demonstrates how Western ideological frameworks influenced Polish cultural identities and shaped local fantasies about Japan and the Orient.
p. 75-92
Keywords: cultural hierarchy; Japanomania; japonisme; Orientalism; universal time; time - anthropological aspects; art, Japanese - Poland; art, Japanese - influence; literature, Japanese - influence; Polish literature - Japanese influences; Japonism - Poland; time perception - history